High entropy modulated quantum paraelectric perovskite for capacitive energy storage - Yongbo Fan; Wanbo Qu; Haifa Qiu; Shuaibing Gao; Lu Li; Zezhou Lin; Yuxuan Yang; Junyi Yu; Lin Wang; Saiwei Luan; Hao Li; Lin Lei; et al. (Nature Communications)
Abstract Electrostatic capacitors are critical components in the power system of electric vehicles (EVs). The current commercially available solutions are largely based on ferroelectric oxides of which the permittivity decrease with increasing electric field. Here, we propose a high entropy modulation design in a quantum paraelectric-ferroelectric/antiferroelectric matrix, which enables a stable and field-independent energy charge/discharge response across a wide voltage range. By effectively synergizing the high efficiency (η) of quantum paraelectrics and the high polarization of the ferroelectric/anti-ferroelectric matrix with the entropy regulator, a high recoverable energy density (Wrec) of 13.3 J cm− 3 with an η of 92.4% is achieved in the bulk state of the perovskite material, promising for device scale-up. Versatile polar regions as well as a defect-less microstructure is achieved by the optimized compositional design and material processing. On a mesoscopic level, the electrical microstructure of the material is engineered to provide a large breakdown strength (E b ) of 750 kV/cm, which is confirmed by the resolved electrochemical information and finite-element simulation. The proposed strategy provides a new path for designing high performance next generation energy storage/power converting dielectrics. This demonstration of quantum paraelectrics for energy storage application is expected to stimulate extensive efforts in the area.